Innovative start-up patenting: A new approach towards identification and determinants - Tina Wolf (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2013)
There already exists broad literature investigating small and innovative firms in many respects. However, there have been few attempts to assess this group of firms propensity to patent or its patenting activities. This paper intends to fill that gap. By applying a new approach to account for young and innovative companies patents, this paper avoids an undercounting of small firm patenting, which has been a feature of most of the earlier studies. A data set is used that comprises information on R&D, capital stock, state promotion etc for 534 Thuringian firms in their first three business years. The results of the zero-inflated negative binomial regression analysis suggest that patenting is an activity of science-oriented, cooperative young firms that are conducting R&D even before the firm has been launched.
Keywords: L25; L26; Q55; 330; entrepreneurship; firm performance; patenting; research and development; technological innovation